Neratinib safety evaluation: real-world adverse event analysis from the FAERS database - Fan, Yunhe; Wu, Teng; Xu, Pengyang; Yang, Chuanli; An, Jie; Zhang, Haijia; Abbas, Mureed; Dong, Xiushan (Frontiers in Pharmacology, 2024)
Aims: Neratinib has emerged as significant theraputic option for breast cancer treatment. However, despite its approval, numerous adverse drug events (ADEs) associated to it remain unrecognized and unreported. This study aims to mine and analyze the signals of ADEs related to neratinib from the US Food and Drug Administration Adverse Event Reporting System (FAERS) database, providing insights for safe and rational clinical use of drug.Methods: All the neratinib-related ADEs data were collected from FAERS database from the third quarter (Q3) of 2017 to the fourth quarter (Q4) of 2023. After standardizing the data, 4 disproportionality methods were used to assess the correlation between neratinib and ADEs.Of the 1,544 ADEs implicating neratinib as the primary suspected drug, a combined total of 48 preferred terms (PTs) and 10 system organ classes (SOCs) showed significant disproportionality accross all four algorithms simultaneously.These SOCs included gastrointestinal disorders (n=2564, ROR 7.14), general disorders and administration site conditions (n=958, ROR 0.77) and injury poisoning and procedural complications (n=474, ROR 0.58) among others. Upon comparison with the neratinib manual, 34 ADEs not documented in the manual were found at the PT level.Our study provide new real-world evidence for drug safety information of neratinib. While the majority of our findings were aligned with the information provided in the manual. We identified additional ADEs not previously documented.Consequently, further studies are needed to validate unreported ADEs to ensure the efficacy and safety of neratinib for patients.